Importance of Campylobacter jejuni FliS and FliW in Flagella Biogenesis and Flagellin Secretion - Radomska, Katarzyna A.; Wösten, Marc M. S. M.; Ordoñez, Soledad R.; Wagenaar, Jaap A.; van Putten, Jos P. M. (Frontiers in Microbiology, 2017)
1 Abstract Flagella-driven motility enables bacteria to reach their favorable niche within the host. The human foodborne pathogen Campylobacter jejuni produces two heavily glycosylated structural flagellins (FlaA and FlaB) that form the flagellar filament. It also encodes the non-structural FlaC flagellin which is secreted through the flagellum and has been implicated in host cell invasion. The mechanisms that regulate C. jejuni flagellin biogenesis and guide the proteins to the export apparatus are different from those in most other enteropathogens and are not fully understood. This work demonstrates the importance of the putative flagellar protein FliS in C. jejuni flagella assembly. A constructed fliS knockout strain was non-motile, displayed reduced levels of FlaA/B and FlaC flagellin, and carried severely truncated flagella. Pull-down and Far Western blot assays showed direct interaction of FliS with all three C. jejuni flagellins (FlaA, FlaB and FlaC). This is in contrast to, the sensor and regulator of intracellular flagellin levels, FliW, which bound to FlaA and FlaB but not to FlaC. The FliS protein but not FliW preferred binding to glycosylated C. jejuni flagellins rather than to their non-glycosylated recombinant counterparts. Mapping of the binding region of FliS and FliW using a set of flagellin fragments showed that the C-terminal subdomain of the flagellin was required for FliS binding, whereas the N-terminal subdomain was essential for FliW binding. The separate binding subdomains required for FliS and FliW, the different substrate specificity, and the differential preference for binding of glycosylated flagellins ensure optimal processing and assembly of the C. jejuni flagellins.